Tilting at wildlife: reconsidering human–wildlife conflict - Redpath, Stephen Mark; Bhatia, Saloni; Young, Juliette (Oryx, 2015)
Conflicts between people over wildlife are widespread and damaging to both the wildlife and people involved. Such issues are often termed human–wildlife conflicts. We argue that this term is misleading and may exacerbate the problems and hinder resolution. A review of 100 recent articles on human–wildlife conflicts reveals that 97 were between conservation and other human activities, particularly those associated with livelihoods. We suggest that we should distinguish between human–wildlife impacts and human–human conflicts and be explicit about the different interests involved in conflict. Those representing conservation interests should not only seek technical solutions to deal with the impacts but also consider their role and objectives, and focus on strategies likely to deliver long-term solutions for the benefit of biodiversity and the people involved.